Changes in ALFF and ReHo values in methamphetamine abstinent individuals based on the Harvard‐Oxford atlas: A longitudinal resting‐state fMRI study. (24th August 2021) - Du, Yanyao; Yang, Wenhan; Zhang, Jun; Liu, Jun
Abstract: Methamphetamine (MA) abuse has become a global public health problem due to damage to various systems throughout the body, especially the central nervous system. However, the differences in resting‐state brain function between short‐term and long‐term abstinence, the pros and cons of treatments, and the relationship between resting‐state brain function and behavioral tests are unknown. Sixty‐three MA abstinent individuals were followed up for nearly 1 year and treated with three different methods. The amplitude of low‐frequency fluctuation (ALFF) and regional homogeneity (ReHo) based on the Harvard‐Oxford atlas (HOA) were measured by resting‐state functional magnetic resonance imaging (fMRI). Impulsivity was evaluated by the Barratt Impulsivity Scale‐11 (BIS‐11). Brain regions with significant increases in ALFF and ReHo values in the long‐term abstinent group compared to the short‐term abstinent group were around the right frontal pole (McKetin et al., 2012, https://doi.org/10.1111/j.1360-0443.2012.03933.x ) and right middle frontal gyrus (Wang et al., 2015, https://doi.org/10.1371/journal.pone.0133431 ). There were no significant differences among the three groups that experienced long‐term abstinence. The changes in ALFF and ReHo in the right middle frontal gyrus were significantly associated with BIS total scores, BIS attention scores, and BIS nonplanning scores. The right middle frontal gyrus is a critical region in MA long‐term abstinent individuals exposed to therapeutic intervention, and this region may be useful, when combined with BIS‐11, as a potential biomarker to identify the effect of abstinence with therapeutic intervention in MA individuals. Abstract : Compared with the short‐term abstinent group, the long‐term abstinent group showed two areas where both amplitude of low‐frequency fluctuation (ALFF) and regional homogeneity (ReHo) values increased: right frontal pole (2) and right middle frontal gyrus (8). The right middle frontal gyrus was associated with Barratt Impulsivity Scale (BIS) total scores, BIS attention scores, and BIS nonplanning scores. Therefore, the right middle frontal gyrus is a critical region, when combined with BIS‐11, as a potential biomarker to identify the effect of abstinence with therapeutic intervention in methamphetamine (MA) individuals.